UNDERSTANDING COMMUNITY’S BEHAVIORAL RESPONSES TOWARDS COVID-19: WHO COMPLY, WHO DON’T AND REASONS OF INCOMPLIANCE - Widyastari, Dyah Anantalia (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2020)
-